"ACEME": Synthesis and characterization of reactive silica residues from two stage mineral carbonation Process. Issue 3 (11th October 2018) - Benhelal, E.; Rashid, M.I.; Rayson, M.S.; Oliver, T.K.; Brent, G.; Stockenhuber, M.; Kennedy, E.M.
Abstract : In this experimental work we synthesized, characterized, and investigated the reactivity of silica‐enriched residue materials produced from low pressure, low temperature dissolution applicable to a two stage mineral carbonation process. XRF and XRD analysis indicated that 66 wt % of silica‐enriched residue (SER) produced from dissolution of heat activated lizardite comprised amorphous silica. We also treated SER with nitric acid to produce amorphous acid treated silica‐enriched residue (ATSER) with over 88 wt % silica. Dissolving these synthesized materials in highly alkaline solution with pH similar to cement paste pore solution for 28 days showed that all synthesized materials displayed some level of Si solubility. ATSER showed the most rapid rate of Si extraction, higher than silica fume (a commercial pozzolanic cement substitute), followed by silica‐enriched residue (SER) which had a faster rate of Si extraction compared with Portland cement as a standard. © 2018 American Institute of Chemical Engineers Environ Prog, 38:e13066, 2019